PEMBERIAN MP- ASI TIDAK BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA ANAK USIA 1- 3 TAHUN DI WILAYAH KERJA PUSKESMAS SUMBANG I KABUPATEN BANYUMAS - Sawitri Dewi; Ikhwah Mu’minah. (Universitas Duta Bangsa Surakarta, 2020)
Stunting is a chronic nutritional problem, meaning that this situation increase as a result of nutritional deficiencies that have accumulated over a long period of time. Age 0-24 months is a critical period in the growth and development of children, because this is the period of the most optimal period of child both for intelligence and physical. WHO / UNICEF recommends 4 important things that must be done, they are: first giving milk to the baby immediately within 30 minutes after birth, second giving only breast milk or exclusive breastfeeding until the baby is 6 months old, third giving complementary feeding (MP-ASI) since the baby aged 6-24 months and fourth continue breastfeeding until the child is 24 months or older. The purpose of this study was to analyze the relationship between Exclusive breastfeeding and complementary feeding (MP-ASI), maternal income and education to the incidence of stunting in the Sumbang I Puskesmas Kabupaten Banyumas.This research is a descriptive analytic using cross sectional design. The population and sample are all children under the age of 12-36 months in the working area of the Puskesmas Sumbang I. Samples were obtained by purposive sampling method. Data collection methods by filling out questionnaires regarding the history of exclusive breastfeeding, MP-ASI and education and income of parents. Stunting data were obtained by measuring the height of a toddler using Microtoice compared to toddler age.The results showed no significant relationship between exclusive breastfeeding (p = 0.372), MP- ASI (p = 0.823), education level (p = 0.979) and family income (p = 0.13) to the incidence of stunting in the region of Puskesmas Sumbang I in Kabupaten Banyumas and all variables are not risk factors for stunting.